2020
DOI: 10.31393/reports-vnmedical-2020-24(3)-15
|View full text |Cite
|
Sign up to set email alerts
|

Modern biomarker cardiotrophin-1 in the diagnosis of myocardial diastolic function in men with essential hypertension

Abstract: Annotation. The aim of the study was to improve the diagnosis of myocardial diastolic function in men with essential hypertension and chronic heart failure with different variants of the cardiotrophin-1 gene. 100 people aged 40–60 were examined: 50 men with asymptomatic essential hypertension and 50 men with essential hypertension complicated by chronic heart failure. Genotyping of the cardiotrophin-1 gene was performed by polymerase chain reaction. Determination of the concentration of cardiotrophin-1 was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It was found that CTF-1 is involved in energy processes; regulation and metabolism of adipose tissue; carbohydrate, lipid metabolism; myocardium remodulation, the development of atrial fibrillation, etc. [4][5][6][7][8].…”
mentioning
confidence: 99%
“…It was found that CTF-1 is involved in energy processes; regulation and metabolism of adipose tissue; carbohydrate, lipid metabolism; myocardium remodulation, the development of atrial fibrillation, etc. [4][5][6][7][8].…”
mentioning
confidence: 99%